Clinical outcome and cerebrospinal fluid profiles in patients with tick-borne encephalitis and prior vaccination history - Lenhard, Thorsten; Ott, Daniela; Jakob, Nurith Juliane; Martinez Torres, Francisco Javier; Grond-Ginsbach, Caspar; Meyding-Lamadé, Uta (Ticks and tick-borne diseases, 2018)
Background - Tick-borne encephalitis (TBE) is endemic in southern and eastern districts of Germany. Approximately 10-14% of the infected individuals suffer from long-term disability and in 1.5-3.6% the course is fatal. Two well-tolerated vaccines are available, which provide high protection and which have been confirmed in several field studies. Here we investigate clinical course, long-term outcome and cerebrospinal fluid (CSF) characteristics of TBE cases with a prior history of any vaccination as well as real vaccination breakthrough (VBT). - Methods - A case series of 11 patients with a prior history of vaccination, part of a recently published lager cohort of 111 TBE cases. Evaluation included clinical data, degree of disability (modified RANKIN scale, mRS) and analysis of CSF and serum samples. Furthermore, metadata for extended analysis on clinical outcome of TBE with VBT were analysed. - Results - One patient had a clear VBT and ten of them had irregular vaccinations schedules (IVS). Infection severity did not differ in patients with IVS as compared to a non-vaccinated control cohort (median mRS: both 3.0) but these patients showed a stronger cellular immune response as measured by CSF pleocytosis (IVS, 205 cells/μL versus non-vaccinated control, 114 cell/μL, P <0.05) and by differential pattern of CSF (intrathecal) immunoglobulin synthesis. However, shift analysis of VBT metadata using linear-by-linear association revealed a more serious course of TBE in patients with VBT than in a non-vaccinated control cohort (χ2=9.95, P=0.002). Furthermore, ordinal logistic regression analysis showed that VBT patients had an age-corrected, 2.65 fold (CI: 1.110-6.328; χ2=4.813; p=0.028) significant higher risk to suffer from moderate or severe infections, respectively. - Conclusion - A history of IVS surprisingly seems to have no impact on the clinical course of TBE but may leave marks in the specific brain immune response. VBT patients, however, carry an age-independent, significant risk to experience a severe infection.